Gut microbiota and HMGB1/NLRP3/GSDMD inflammasome-dependent pyroptosis: mechanisms by physcion ameliorates alcoholic liver fibrosis - Bai, Ting; Guo, Hao-Lin; Wang, Fei; Kang, Yan-Yu; Zhang, Hao-Tian; Dong, Lu; Yang, Yong (Frontiers in Pharmacology, 2025)
Alcoholic liver fibrosis (ALF) developed from long-term excessive alcohol consumption, which causes inflammatory reactions, lipid accumulation and cirrhosis. An imbalance in gut microbiota is a crucial driving factor for liver fibrosis through the gut-liver axis. This study aimed to explore the effect of physcion on ALF associated with HMGB1/NLRP3 pathways and gut microbiota. C57BL/6 mice were used to establish animal model of ALF, LX-2 cells were used to establish alcohol-activated cell model, the intestinal contents of the mice were collected and analyzed by 16S rRNA sequencing. Physcion effectively ameliorated ALF-induced inflammation, collagen deposition, lipid accumulation by SirT1, AMPK phosphorylation and SREBP1 expression. Moreover, pyroptosis-related proteins (Caspase-1, IL-1β, GSDMD) were significantly reduced after physcion treatment. Interestingly, the diversity of intestinal bacteria and the abundance in physcion treatment mice was significantly higher, while the abundance of harmful bacteria was significantly lower than that in ALF mice. Importantly, it was found that physcion inhibit HMGB1/NLRP3 pathways both in vivo and in vitro, and suppress accumulation of extracellular matrix by inhibiting Collagen-I and α-SMA to finally reverse hepatic stellate cells activation. Continuous administration of HMGB1 and NLRP3 inhibitors showed hepato-protection in alcohol-activated LX-2 model. siRNA-mediated knock-down in LX-2 cells of HMGB1 significantly impaired physcion-mediated protection. Regulation of the HMGB1/NLRP3 pathway recovered hepatic injury and further contributed to physcion’s beneficial effects. Taken together, the results reveal that physcion diminishes HMGB1/NLRP3 inflammasome/pyroptosis and that this diminishment is hepato-protective against ALF.